Original paperINFLUENCE OF A LOW-DOSE COX-2 INHIBITOR DRUG ON EXERCISE-INDUCED INFLAM- MATION, MUSCLE DAMAGE AND LIPID PEROXIDATION - Khoshkhahesh, F.; Siahkuhain, M.; Fisher, G.; Nakhostin-Roohi, B. (Biology of Sport, 2013)
The purpose of this study was to examine the effect of acute low-dose celecoxib administration on exercise-induced inflammation, muscle damage and lipid peroxidation. Twenty healthy untrained males (age: 25.5±4.5 yrs, weight: 72.7±7.9 kg, height: 177.3±7.2 cm) were randomly assigned to treatment (T) or placebo (P) groups. Blood samples were obtained before, immediately after, 3 h after and 24 h after exercise. Subjects · ran for 30 min at 75% VO2max on a treadmill. Participants consumed 100 mg celecoxib or a placebo immediately after and 12 h after the immediately post-exercise blood sample. Total leukocytes, neutrophils, creatine kinase (CK), C-reactive protein (CRP) and malondialdehyde (MDA) were assessed at each time point. Significant increases in total leukocytes and neutrophils were observed 3 h after exercise in both groups (P<0.05). CK and CRP levels were significantly increased immediately, 3 h and 24 h after exercise in both groups (P<0.05). A significant increase in MDA was observed immediately after exercise in both groups (P<0.05); however, no significant group differences were observed for MDA or CK. These findings suggest that inhibition of cyclo-oxygenase activity with low-dose celecoxib does not affect exercise-induced inflammation, muscle damage, or lipid peroxidation.